Peningkatan Kuantitas dan Kualitas Pertanyaan Siswa melalui Penerapan Model PBL disertai Dialog Socrates di Kelas X Mia 4 SMA Negeri Gondangrejo - Jumiati, Jumiati; Muzzazinah, Muzzazinah; Suciati, Suciati (Universitas Sebelas Maret, 2017)
The objective of research was to improve the question’s quantity and quality student’s through the application of PBL using dialogue Socratic model at grade X MIA 4 of State Senior High School Gondangrejo. The result of the pre-cycleobservation shows that the quality of the question are 6 question. The quality of the question is in the C2 thinking level while according to the knowledge dimension is un the conceptual knowledge dimension. Mostly, the students thinking skill were low. So that, it needed to be improved. This study was a Classroom Action Research (CAR) conducted in two cycle. Subject were 36 students of X MIA 4 State Senior High School Gondangrejo. The steps of the research were planning, acting, and reflecting in each cycle. Data collected through observation, interview, and documentation. The data validation used triangulation method, and then were analized using qualitative-descriptive analysis technique. The improvement of the quantity and the quality of students question indicated by 6 question of pre-cycle activities with conceptual C2 as the best question quality, became 54 questions with procedural C3 as the highest questions quality within first cycle and 70 questions with metacognition C2 as the highest questions quality within the final cycle. The conclusion of research was the application of PBL using dialogue Socratic model improve the quantity and quality of question student at grade X MIA 4 State High School Gondangrejo.